2013
DOI: 10.1007/s13592-013-0254-1
|View full text |Cite
|
Sign up to set email alerts
|

Heterochrony of cuticular differentiation in eusocial corbiculate bees

Abstract: -The exoskeleton (cuticle) of insects varies widely in shape, biomechanical properties, and functions, which are inherent to the biological species and developmental stage, besides showing a wealth of architectural specializations and nuances in the different body regions. The morphological pattern of exoskeleton maturation was studied in eusocial and solitary bees, including species of all three eusocial tribes of corbiculate bees as follows: Apini, Meliponini, and Bombini. The results showed striking differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…In the social insects, the cuticle is not yet mature after the last change. The body cuticle is completely mature only in older individuals and the more abundant CHs are alkanes, followed by alkenes, alkadienes, and methyl alkenes (Elias-Neto et al 2013;Falcon et al 2014;Kather and Martin 2015). Our findings for the CH profiles in M. scutellaris virgin queens show differences from those reported for this stingless bee by Kerr et al (2004), which were rich in tricosane contrasting with hentricontene as described here, which may be due to different CH extraction procedures, given that those authors only used the bee's wings.…”
Section: Discussioncontrasting
confidence: 75%
“…In the social insects, the cuticle is not yet mature after the last change. The body cuticle is completely mature only in older individuals and the more abundant CHs are alkanes, followed by alkenes, alkadienes, and methyl alkenes (Elias-Neto et al 2013;Falcon et al 2014;Kather and Martin 2015). Our findings for the CH profiles in M. scutellaris virgin queens show differences from those reported for this stingless bee by Kerr et al (2004), which were rich in tricosane contrasting with hentricontene as described here, which may be due to different CH extraction procedures, given that those authors only used the bee's wings.…”
Section: Discussioncontrasting
confidence: 75%
“…In this context, we draw our attention to the fact that bees greatly vary in the grade of cuticle melanization/sclerotization at the emergence time (adult ecdysis). In a previous study on the morphology of the developing adult cuticle [34], we observed that in eusocial bees, but not in the solitary ones, the process of cuticle melanization/sclerotization leading to cuticle maturation is extended to the adult stage. After emergence, workers from eusocial species (including the primitively eusocial bees from Bombini) spend some days performing inside nest activities, and during this period they stay protected in a safe and provisioned environment [35] where the hygienic behavior provides a certain level of immunity [36].…”
Section: Introductionmentioning
confidence: 73%
“…As is known, physicochemical properties of cuticle are highly affected by extraction method (Thomson et al 2004). The exoskeleton (cuticle) of insects varies widely in shape, biochemical properties and fuctions, which are inherent to the biological species, developmental stage, besides showing, wealth of architectural specialization and nuances in the different body regions (Elias-Neto et al, 2014).…”
Section: Resultsmentioning
confidence: 99%